Disharmony of Criminal Norms in Accountability for Illegal Skincare Distribution in Digital Marketplaces - Lulut Dyah Wardani; Suryawan Raharjho (Journal of Mathematics Instruction, Social Research and Opinion, 2026)
The rapid growth of digital marketplaces in Indonesia has intensified the circulation of illegal skincare products, posing public health risks and undermining criminal enforcement. Prior studies focus mainly on civil and administrative consumer protection, leaving criminal norm disharmony underexplored. This study analyzes criminal norm construction, identifies normative disharmony, and reconstructs criminal liability for illegal skincare distribution in digital marketplaces. A normative juridical approach was applied through statutory, conceptual, and case-based analysis of primary, secondary, and tertiary legal materials. Findings reveal that criminal norms remain partial and sectoral, producing norm conflicts, overlapping regulations, and regulatory gaps—particularly concerning digital platform intermediaries and anonymous perpetrators. Normative disharmony is the primary obstacle to effective law enforcement. Reconstructing criminal liability through expanded legal subjects, corporate criminal liability, limited strict liability, and regulatory harmonization across the Health Law, Consumer Protection Law, and ITE Law is essential to strengthen legal certainty and consumer protection.